2020
DOI: 10.3389/fcell.2020.00344
|View full text |Cite
|
Sign up to set email alerts
|

A Set of Global Metabolomic Biomarker Candidates to Predict the Risk of Dry Eye Disease

Abstract: Purpose: We used ultraperformance liquid chromatography coupled with quadrupole/time-of-flight tandem mass spectrometry (UPLC-Q/TOF-MS/MS) to analyze the metabolic profile of reflex tears obtained from patients with dry eye disorders. Methods: We performed a cross-sectional study involving 113 subjects: 85 patients diagnosed with dry eye syndrome (dry eye group) and 28 healthy volunteers (control group). Reflex tears (20-30 µl) were collected from the tear meniscus of both eyes of each subject using a Schirmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
2
10
2
Order By: Relevance
“…In recent years, with the aging of the population, the use of electronic devices, and environmental factors, the number of patients with dry eye has been on the rise [19][20][21][22] . At present, there are various ways to treat dry eye, mainly including the elimination of incentives, arti cial tear replacement therapy, preservation of own tears, promotion of tear secretion, further combining anti-in ammatory and immunosuppression, and surgical treatments [23][24][25] . However, general incentives are di cult to eliminate, and due to the complex composition of human tears, although there are various arti cial tears for different tear lm components, they still cannot completely replace their own tears.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the aging of the population, the use of electronic devices, and environmental factors, the number of patients with dry eye has been on the rise [19][20][21][22] . At present, there are various ways to treat dry eye, mainly including the elimination of incentives, arti cial tear replacement therapy, preservation of own tears, promotion of tear secretion, further combining anti-in ammatory and immunosuppression, and surgical treatments [23][24][25] . However, general incentives are di cult to eliminate, and due to the complex composition of human tears, although there are various arti cial tears for different tear lm components, they still cannot completely replace their own tears.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies did not report any significant age-related effect on the ω3:ω6 (proinflammatory/antiinflammatory) lipid ratio in tears 88 nor on amino acids 53 whereas most studies found that concentrations of both lipids 48,3,5 and metabolites 76,43 were influenced by age.Other factors (e.g.…”
Section: B) Other Factors Influencing Tear Metabolome and Lipidomementioning
confidence: 95%
“…In most studies, tear fluid is obtained after cutting the Schirmer strip into multiple pieces (size ranging from 2 to 10mm) and placed in a vial which is centrifuged 49,47,46,48,3,26,[4][5][6] . In contrast, entire Schirmer strip extraction using a solvent 18,23,43 or punches of 4mm in diameter of the front end of the Schirmer strip 29 represent alternative procedures.…”
Section: -Absorbent Materialsmentioning
confidence: 99%
“…Moreover, in terms of the high-throughput profiling of the whole metabolome in a disease condition, identifying biomarkers becoming possible ( 18 , 19 ). With advances in technology, untargeted LC–MS metabolomic analysis of tear fluid has been applied in clinical and animal studies of several eye diseases, such as keratoconus ( 12 , 15 , 20 ), dry eye ( 13 , 21 ), and multiple sclerosis ( 16 ). Studies of metabolomics used in eye diseases have been summarized in a recent review article ( 12 ).…”
Section: Introductionmentioning
confidence: 99%